2006
DOI: 10.1007/s10661-006-4940-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Source Identification and Apportionment of Selected Metals in TSP in an Urban Atmosphere

Abstract: To understand the metal distribution characteristics in the atmosphere of urban Islamabad, total suspended particulate (TSP) samples were collected on daily 12 h basis, at Quaid-i-Azam University campus, using high volume sampler. The TSP samples were treated with HNO(3)/HClO(4) based wet digestion method for the quantification of eight selected metals; Fe, Zn, Pb, Mn, Cr, Co, Ni and Cd by FAAS method. The monitoring period ran from June 2001 to January 2002, with a total of 194 samples collected on cellulose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 48 publications
3
21
0
3
Order By: Relevance
“…It is seen that while the total particulate matter concentration increased in fall, the overall heavy metal content decreased except for Ni at NFI site. Similar and higher concentration of heavy metal contents in particulate matter in summer has been reported in literatures (Espinosa, Ternero Rodríguez, De La Rosa, & Sánchez, 2001;Gupta, Salunkhe, & Kumar, 2010;Querol et al, 2006;Razos & Christides, 2010;Shah, Shaheen, & Jaffar, 2006;Smichowski et al, 2004).…”
Section: Heavy Metals Distribution In Particlessupporting
confidence: 86%
“…It is seen that while the total particulate matter concentration increased in fall, the overall heavy metal content decreased except for Ni at NFI site. Similar and higher concentration of heavy metal contents in particulate matter in summer has been reported in literatures (Espinosa, Ternero Rodríguez, De La Rosa, & Sánchez, 2001;Gupta, Salunkhe, & Kumar, 2010;Querol et al, 2006;Razos & Christides, 2010;Shah, Shaheen, & Jaffar, 2006;Smichowski et al, 2004).…”
Section: Heavy Metals Distribution In Particlessupporting
confidence: 86%
“…As a consequence of the growing interest of the scientific community in chemical composition of particulates we started an extended study on TSP to obtain statistically significant data on its trace metal constituents. Indeed, previous short-term studies carried out in this area (Shah et al 2004(Shah et al , 2006Shaheen et al 2005a, b) revealed elevated levels of some toxic trace metals over a particular duration but so far no study has been reported on their annual and seasonal variations. These data stress the importance of a deeper knowledge of TSP composition, as well as their emission sources and of the role of atmospheric dispersion conditions in the area.…”
Section: Introductionmentioning
confidence: 87%
“…The overall distribution of metals in the TSP samples remained, in general, far from a normal distribution, as projected by the skewness values, notably high for Cu, Co, Sr, Sb, Mg, Cr, Mn and Pb. This indicated a non-normal metal distribution influenced by an uptake and/or depletion of metals in particulate matter by random processes (Shah et al 2006;Shaheen et al 2005a;Kim et al 2002a;Samura et al 2003); the attributes to these could be traced in anthropogenic sources that are examined in the forthcoming sections. The percentile distributions of the selected metals are also presented as box and whisker plot in Fig.…”
Section: Airborne Metal Distribution For the Annual Periodmentioning
confidence: 97%
“…In addition, a broad range of chemical species, ranging from elemental to organic and inorganic compounds, attached to SPM also have negative effects on human health (Fergusson 1990;Dasilva and Williams 1991;Moreno et al 2007; Gupta et al 2007). Among the inorganic compounds, the most important are the trace elements which originate from outdoor sources, such as crustal materials, road dust, construction activities, fossil fuel combustion, vehicular traffic, industrial emissions, and indoor sources, such as building and decorating materials, smoking, and cooking (Willers et al 2005;Ahmed and Ishiga 2006;Shah et al 2006;Liu et al 2009). For instance, lead could impact the nervous system and cause impairment of the immune system and insomnia (Canfield et al 2003;Järup 2003;Bouchard et al 2007), and arsenic could the gastrointestinal tract, respiratory tract, hematopoietic and nervous systems (Al Rmalli et al 2005).…”
Section: Introductionmentioning
confidence: 99%